Retinal arterial macroaneurysm: a case report - Chaudhary, Sushma; Gupta, Sharad; Yadav, Reena; Gupta, Vidisha; Shrestha, Satbodh; Bista, Bipin (Journal of Chitwan Medical College, 2021)
Retinal arterial macro-aneurysms are pathological dilatations of retinal arterial branches mostly found in posterior pole. Here we present a 51 years old female with a diagnosis of retinal artery macro-aneurysm in the superior temporal arcade associated with macular edema based on clinical and optical coherence tomography (OCT) finding. Patient was treated with intra-vitreal injection (1.25 mg in 0.05 ml) of anti-vascular endothelium growth factor (bevacizumab) which showed both improvement in visual acuity and resolution of macular edema. Intra-vitreal injection of bevacizumab (Avastin) is safe and effective in treatment of macular edema associated with retinal arterial macro-aneurysms.